2019
DOI: 10.3390/ijerph17010148
|View full text |Cite
|
Sign up to set email alerts
|

Stress Recovery of Campus Street Trees as Visual Stimuli on Graduate Students in Autumn

Abstract: Human stress recovery response to landscapes is under discussion in Chinese settings. The present study aimed to clarify the stress recovery effects of campus street trees on graduate students in autumn. A total of 150 participants (23.75 ± 1.01 years old) completed the Trier Social Stress Test (TSST) and were then randomly assigned to view one of five virtual environments, including the street trees Sophora japonica, Ginkgo biloba, Platanus acerifolia, Koelreuteria paniculata, and the indoor environment (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 53 publications
2
44
0
3
Order By: Relevance
“…This tends to infer that states of relaxation and concentration can occur simultaneously to some extent. These findings are consistent with related research on emotional changes caused by environmental contact, including virtual visual stimulation experiments ( Guo et al, 2020 ), walking in a bamboo forest and a city environment ( Hassan et al, 2018b ), and horticultural activity ( Hassan et al, 2018a ), etc. These studies consistently reported higher mean alpha and beta values, reflecting relatively higher levels of relaxation and attention.…”
Section: Discussionsupporting
confidence: 92%
“…This tends to infer that states of relaxation and concentration can occur simultaneously to some extent. These findings are consistent with related research on emotional changes caused by environmental contact, including virtual visual stimulation experiments ( Guo et al, 2020 ), walking in a bamboo forest and a city environment ( Hassan et al, 2018b ), and horticultural activity ( Hassan et al, 2018a ), etc. These studies consistently reported higher mean alpha and beta values, reflecting relatively higher levels of relaxation and attention.…”
Section: Discussionsupporting
confidence: 92%
“…If there is green space within walking distance of the residence, it can lead to an increase in the longevity of senior citizens [ 13 ]. As a more direct effect, contact with nature promotes psychological restoration [ 16 ] and reduces stress [ 17 , 18 ]. Moreover, brief walking in an urban green space, as opposed to that in a city area, induces psychological as well as physiological relaxation, as evidenced by suppressed sympathetic nervous system activity, improved parasympathetic nervous system activity, improved mood state, reduced anxiety levels, and decreased heart rate [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al reported that Ginkgo biloba and Platanus acerifolia, both of which have golden yellow leaves, showed significant differences in stress recovery whereas Ginkgo biloba and Sophora japonica, which both have gray-brown bark but different leaf colors, showed similar ability to decrease stress. However, that study did not consider the possibility of psychological effects caused by different colors on the trunk [55]. In addition, Kuper found that people prefer flowering plants or red, yellow, and autumn-colored foliage, which also have increased psychophysiological effects [56], while Kaufman and Lohr demonstrated that people prefer trees with green and red leaves to those with orangebrown leaves [52].…”
Section: Effects Of Color Variation and Organ Expression Of Plants On Humansmentioning
confidence: 93%